The Coming Crisis (Building a Sustainable Political Economy: SPERI Research & Policy, 2018)
This book provides a timely warning of the dangers still present and building in the global economic system, whose frailty was exposed by the global financial crisis, and the Eurozone crisis it spawned. The contributors to this volume draw on SPERI's work on the political economy of growth, stagnation, austerity and crisis, and placing each in the context of the wider environmental crisis. .